Predictors of communal formation in a small heavy metal scene: Puerto Rico as a case study. (1st October 2014) - Varas-Díaz, Nelson; Rivera-Segarra, Eliut; Medina, Carmen L. Rivera; Mendoza, Sigrid; González-Sepúlveda, Osvaldo
Heavy metal music has constantly been under scrutiny due to its perceived negative effects on its listeners. Quantitative research has focused on heavy metal music as a risk factor for mental health problems and antisocial behaviour. This research agenda has neglected to explore and quantitatively document how the music can foster positive outcomes among its listeners, in particular a strong sense of community. Fans and producers of heavy metal music constantly reference community as an important aspect of the sonic experience. Still, few studies have addressed the communal experience in heavy metal music from a quantitative perspective. Therefore, the specific aims of this study were to (1) document levels of sense of community among members of the Local Metal Scene (LMS) in Puerto Rico, (2) explore differences on sense of community among core scene members and those at its periphery, and (3) explore predictive variables that can explain sense of community among its members. We present data from a larger study of the metal scene in Puerto Rico, which used a mixed methods approach including ethnographic observations, qualitative interviews and surveys with members of Puerto Rico's metal scene. Results evidence high levels of sense of community, with existing differences among members of the same scene. Furthermore, our results identify six predictive variables of importance for sense of community among the LMS in Puerto Rico.